Hubungan antara Tingkat Spiritualitas dengan Kesiapan Lanjut Usia dalam Menghadapi Kematian Di Desa Pucangan Kecamatan Kartasura - Sari, Eka Dino Gusvita, Agus Sudaryanto, S.Kep., Ns., M.Kes, Faizah Betty R., A., S.Kep ., M.Kes (2015)
Death was feared by most elderly. Elderly who were ready to face death means that the integrity of the ego had been reached, so it could improve the quality of live in elderly. One of the factors that may affect the readiness of the elderly in the face of death was spirituality. A high level of spirituality in the elderly can provide a sense of calm and comfortable in the face of death and can improve the quality of life in elderly. The purpose of this study was to know the correlation between spirituality with readiness to face death in elderly in Pucangan Village Kartasura Sub-district. This research was a descriptive correlative research with cross sectional design. Population of this research were 1.668 elderly listed in posyandu elderly in Pucangan Village, the number of samples taken amounted to 95 respondents. The sampling technique used was proportional sampling. The research instrument used was a The Spiritual Involvement and Beliefs Scale developed by Hatch and a questionnaire readiness to face death. Analysis of the data used was Fisher's Exact test. The survey results revealed that elderly people were ready to face death have high level of spirituality. The results of this research was evidenced by the result of the analysis of Fisher's Exact test, which showed the value of p-value = 0.017, which means that Ho was rejected. The conclusions from this research there was a relationship between the level of spirituality with readiness to face death in Elderly in Pucangan Village Kartasura Sub-District